2005
DOI: 10.1093/ps/84.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole residues in chicken tissues and eggs

Abstract: Levamisole is currently being used to treat capillaria infection in chickens even though there is no published withdrawal information available for levamisole in chickens. Tissue residue withdrawal of levamisole in chickens was studied in 32 healthy broiler breeder chickens at the age of 32 wk (peak of egg production). Levamisole residues in chicken tissues, eggs, and plasma were determined by HPLC with ultraviolet (UV) detection at 225 nm. The highest level of residue and longest withdrawal after oral adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In chickens, a dose of Levamisol three-times greater than the one we used was undetectable in plasma after three days (El-Kholy and Kemppainen, 2005). In other species, Levamisol was found to have an immunomodulatory effect [e.g.…”
Section: Experimental Protocolmentioning
confidence: 97%
“…In chickens, a dose of Levamisol three-times greater than the one we used was undetectable in plasma after three days (El-Kholy and Kemppainen, 2005). In other species, Levamisol was found to have an immunomodulatory effect [e.g.…”
Section: Experimental Protocolmentioning
confidence: 97%
“…[31,60,[71][72][73][74][75][76] Studies have conferred the prevalence of higher concentrations of levamisole residues in liver of broiler chickens as compared to other body tissues, including thigh muscles, due to the lipid-soluble nature of the drug. [30] Moreover, the deposition of oxytetracycline and chloramphenicol residues in substantially higher amounts within the liver and kidney samples of broilers confirmed by Salehzadeh et al [63] and Shahid et al [71] indicated non-compliance of established MRLs. Similarly, higher concentrations of ciprofloxacin and enorfloxacin residues in livers and kidneys of broiler chickens along with relatively lower concentrations of flumequine have also been detected.…”
Section: Drug Residues In Meatmentioning
confidence: 92%
“…In mammals, levamisole is well absorbed when given orally and is excreted relatively rapidly in the urine (Barragry, 1984a). There are no data available on the absorption or primary excretion pathways of levamisole in birds, but the drug concentrates in the liver following oral dosing in chickens (FAO/WHO, 1991), and residues are found in the eggs of laying hens for up to 2 weeks after treatment (El‐Kholy & Kemppainen, 2005).…”
Section: Overview Of the Drug Classesmentioning
confidence: 99%